Effects of plastic pre-straining level on the creep deformation, crack initiation and growth behaviour of 316H stainless steel - Mehmanparast, Ali; Davies, C. M.; Dean, David W.; Nikbin, Kamran (Elsevier, 2016)
The effects of the material pre-straining level, in the form of plastic pre-compression at room temperature, on the tensile, creep deformation, creep crack initiation and growth behaviour of 316H stainless steel have been examined at 550 °C. Experiments have been performed on the 4%, 8% and 12% pre-compressed specimens and the results are compared with existing data on the pre-compressed material to investigate the change in mechanical response, creep failure, creep crack initiation and growth behaviour of 316H over a range of plastic pre-straining levels. Comparisons are also made to short term and long term test data on the as-received material. It has been found that creep ductility and rupture times decreased with an increase in pre-strain levels considered. The test results obtained from different material states are discussed in terms of the influence of material pre-straining level on the microstructural deformation, mechanical response, creep deformation and crack growth behaviour of the material.
Keywords: Pre-straining level; Pre-compression; CCG; Creep ductility; Long term creep; 316H